BREEDING POTENTIAL OF RICE GENOTYPES IN TWO AGROCLIMATIC CONDITIONS OF SULAIMANI - KURDISTAN REGION - IRAQ - D. A. Abdulkhaleq, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to investigate the genetic variability of 26 rice genotypes and evaluation at two locations in Sulaimani governorate, Gaba and Chawtan which were completely different in their environmental condition during the season of 2019. The performances of the genotypes were analyzed at both locations as well as the average of both. Simple coefficients of correlation were used to assess the grain yield components and their relationships. Path analysis was used to determine the direct and indirect effects of such components on grain yield plant-1. The genotypes were grouped based on the agro-morphological features using cluster analysis. Almost all of the traits at both locations and the average of both locations showed highly significant differences; Chawtan outperformed Gaba location for the traits no. of tillers plant-1, no. of panicle plant-1, 1000-grain weight, and plant-1 grain yield, whereas higher values were found for plant height and no. of grains panicle-1 for Gaba location. At both locations, there was a highly significant and positive association between the number of tillers and panicles in plant-1 and grain yield plant-1. The number of panicle plants-1 had the most favorable direct effects on grain yield at both locations. At both locations, the highest positive indirect effect on grain output was provided by the number of tillers plant-1 via the number of panicle plant-1. Based on the agro-morphological features, the rice genotypes were grouped into 5 clusters at both locations. At both locations, Cluster V gave better values regarding grain yield.